2019
DOI: 10.22237/jmasm/1553610953
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Likelihood Estimation for the Generalized Pareto Distribution and Goodness-of-Fit Test with Censored Data

Abstract: A non-parametric efficient statistical method, Random Forests, is implemented for the selection of the determinants of Central Bank Independence (CBI) among a large database of economic, political, and institutional variables for OECD countries. It permits ranking all the determinants based on their importance in respect to the CBI and does not impose a priori assumptions on potential nonlinear relationships in the data. Collinearity issues are resolved, because correlated variables can be simultaneously consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
(27 reference statements)
2
3
0
Order By: Relevance
“…Hence, although trade openness could reduce the CBI, as D'Amato et al (2009) suggested, it is not statistically important in explaining the degree of CBI in the Asia-Pacific countries examined in this paper. The income level represented by the real income per capita level has been statistically significant in lowering the CBI of the sample, supporting the empirical results of Dincer and Eichengreen (2014) and the theoretical assumptions of Cavicchioli et al (2019) andD'Amato et al (2009) mentioned above. Additionally, the lagged inflation has a negative sign and is statistically insignificant in all models.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Hence, although trade openness could reduce the CBI, as D'Amato et al (2009) suggested, it is not statistically important in explaining the degree of CBI in the Asia-Pacific countries examined in this paper. The income level represented by the real income per capita level has been statistically significant in lowering the CBI of the sample, supporting the empirical results of Dincer and Eichengreen (2014) and the theoretical assumptions of Cavicchioli et al (2019) andD'Amato et al (2009) mentioned above. Additionally, the lagged inflation has a negative sign and is statistically insignificant in all models.…”
Section: Resultssupporting
confidence: 78%
“…(2009) suggested, it is not statistically important in explaining the degree of CBI in the Asia–Pacific countries examined in this paper. The income level represented by the real income per capita level has been statistically significant in lowering the CBI of the sample, supporting the empirical results of Dincer and Eichengreen (2014) and the theoretical assumptions of Cavicchioli et al. (2019) and D'Amato et al.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations